Control of nozzle flow using rectangular ribs at sonic and supersonic mach numbers - Sethuraman, Vigneshvaran; Rajendran, Parvathy; Khan, Sher Afghan; Aabid, Abdul; Baig, Muneer (Tech science Press, 2024)
This study deals with base pressure management in a duct for various values of the Mach number (M), namely, the Mach number corresponding to sonic and four supersonic conditions. In addition to the Mach number, the nozzle pressure ratio (NPR), the area ratio, the rib dimension, and the duct length are influential parameters. The following specific values are examined at M = 1, 1.36, 1.64, and 2, and NPRs between 1.5 and 10. The base pressure is determined by positioning ribs of varying heights at predetermined intervals throughout the length of the square duct. When the level of expansion is varied, it is seen that the base pressure initially drops for overexpanded flows and increases for under-expanded flows. When ribs are present, the flow field in the duct and pressure inside the duct fluctuate as the base pressure rises. Under-expanded flows can achieve a base pressure value that is suitably high without experiencing excessive changes in the duct flow in terms of static pressure if a rib height of around 10% of the duct height close to the nozzle exit is considered. Rectangular rib passive control does not negatively affect the duct’s flow field.